The Notion of Subjective and Objective Modality in Language - T. A. Selezneva (Vestnik MGIMO-Universiteta)
The purpose of this article consists in giving a general notion of the categories of subjective and objective modality in language. The author notices and summarizes the most important theoretical approaches to the problem of objectivity and subjectivity in russian and foreign linguistics